Some Personal and Organizational Determinants Of Job Satisfaction Of Postal Clerks - Carrell, Michael R.; Elbert, Norbert F. (Academy of Management Journal, 1974)
The article investigates the personal and organizational variables which determine the job satisfaction of postal clerks. Age, education and home environment were found to have significant main effects. There was inverse relationship between education level and satisfaction, with the college graduates being the least satisfied and those with less than a high school diploma being the most satisfied. Clerks with an urban home environment were less satisfied than those with rural home environment. In addition, location was found to have a significant main effect.